Word ‘Yasno’ [Clear] as a Lexical-Syntactic Marker of Linguistic Personality in Novel “We” by E. Zamyatin - O. V. Shatalova (Научный диалог, 2022)
The question of the linguistic personality description of the character of a work of art through the analysis of lexical and syntactic markers is considered. A review of the main trends in the development of the theory of linguistic personality is made, which determine the objectivity of identifying a lexical-syntactic marker as a unit that integrates linguistic units of various levels. The analysis results of the functioning of the word ‘yasno’ [clear], which marks the linguistic personality of the protagonist of the novel “We” by E. Zamyatin, are presented. The functional and pragmatic potential of the marker in the objectification of the intellectual, emotional and moral intentions of the D-503 character in the retrospective of the entire work is determined. The presence of contextual changes in semantics, morphological qualification, syntactic and punctuation well-formedness of the lexico-syntactic marker ‘yasno’ [clear] is proved. There is a relationship between the variation of the lexical environment of this word and the emotional and mental state of the character. The novelty of the research is seen in the fact that the semantic and grammatical transformation of the lexical-syntactic marker of the character's linguistic personality is revealed, indicating a modification of the personality within the framework of the plot.